Characterization of primary afferent spinal innervation of mouse uterus - Herweijer, Geraldine; Kyloh, Melinda; Beckett, Elizabeth A. H.; Dodds, Kelsi N.; Spencer, Nick J. (Frontiers in Neuroscience, 2014)
The primary afferent innervation of the uterus is incompletely understood. The aim of this study was to identify the location and characteristics of primary afferent neurons that innervate the uterine horn of mice and correlate the different morphological types of putative primary afferent nerve endings, immunoreactive to the sensory marker, calcitonin gene related peptide (CGRP). Using retrograde tracing, injection of 5-10µL of 1,1'-didodecyl-3,3,3,3'-tetramethylindocarbocyanine perchlorate (DiI) into discrete single sites in each uterine horn revealed a biomodal distribution of sensory neurons in dorsal root ganglia (DRG) with peak labelling occurring between T13-L3 and a second smaller peak between L6-S1. The mean cross sectional area of labelled cells was 463 µm2 +/- SEM. A significantly greater proportion of labelled neurons consisted of small cell bodies (<300 µm2) in the sacral spinal cord (S2) compared with peak labelling at the lumbar (L2) region. In both sections and whole mount preparations, immunohistochemical staining for CGRP revealed substantial innervation of the uterus by CGRP-positive nerve fibres located primarily at the border between the circular and longitudinal muscle layers (N=4). The nerve endings were classified into three distinct types: “single”, “branching” or “complex”, that often aligned preferentially in either the circular or longitudinal axis of the smooth muscles. Complex endings were often associated with mesenteric vessels. We have identified that the cell bodies of primary afferent neurons innervating the mouse uterus lie primarily in DRG at L2 and S1 spinal levels. Also, the greatest density of CGRP immunoreactivity lies within the myometrium, with at least three different morphological types of nerve endings identified. These findings will facilitate further investigations into the mechanisms underlying sensory transduction in mouse uterus.